Pemahaman Konsep Siswa: Eksperimen pada Siswa SMP dengan Pembelajaran Matematika Berbasis Kooperatif Tipe Conceptual Understanding Procedures (CUPS) - Tri Bondan Kriswinarso; Lis Sugianto; Saiful Bachri (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2023)
The cooperative learning model of the Conceptual Understanding Procedures (CUPs) type is a learning model in which students are instilled in how to make conclusions on the material being studied. In addition, the CUPs cooperative learning model is based on a constructivism approach based on the belief that students construct conceptual understanding by expanding or modifying existing knowledge. This research is experimental research which aims to find out the conceptual understanding of class VII students of SMP Negeri 6 Palopo who apply the CUPs type cooperative model. The population in the study were all class VII students of SMP Negeri 6 Palopo. The data collection was carried out in 2 stages, namely the preparation stage and the data collection stage. The analysis used in this study was descriptive statistical analysis and inferential statistical analysis. The average value of gain in the experimental class is 0.78 which is in the high category while the average value of gain in the control class is 0.66 which is in the medium category. In the sig column (2-tailed) the probability value is 0.000 less than the significant value α = 0.05, then H0 is rejected and H1 is accepted, so it can be concluded that there is a difference in the increase in the ability to understand mathematical concepts of students who are taught using the CUPs type cooperative learning model and conventional learning.